MEDIAÇÃO DO CINEMA BRASILEIRO: o gênero comédia e a linguagem cinematográfica como categorias mediadoras dos filmes longa-metragem nacionais no período da Retomada (1993-2013) - ARANHA, Stella Pereira (2014)
This lecture discuss how the comedy and the cinematographical language work as intermediary cathegories of Brazilian cinema. It shows a theorical review about an interdisciplinary perspective that envolves art, communication and sociology, clearing the various meanings of the term mediation. It defines by what point of view the mediation of Brazilian cinema is broached at this research. It explains how the public become familiar with the esthetics of TV language, transposed to the Brazilian movies, it stipulates the look of the spectator in the country. It establishes how the humor tradition is one of the most best received cultural manifestation by Brazilian spectator, demonstrating how comedy, in the history of the cinema in Brazil, developed a way of operation to make the sector lucrative in progressive humor cycles on national cinema. It relates the difficulties found in the research, reinforcing the confirmation of the inicial theories and indicating the courses to continue the investigation.